Beyond the written word: Newspapers as critical literacy teaching tools in the South African classroom - Rockie Sibanda (Universitas Ahmad Dahlan, 2021)
This paper provides the rationale and purpose for a critical literacy awareness strategy, implemented to 20 English second language students at a township secondary school in South Africa. This empirical study provides insight into using newspapers as a pedagogical tool to develop students’ language and critical literacy skills. Using different classroom activities and class discussions, the teacher helped the students to read beyond different texts and raised their awareness of different ideologies that inform texts. Working in pairs and groups, the learners engaged with different genres of texts. In this study, special emphasis is promoting critical thinking for social justice where critical literacy is used as a tool to better understand and improve the world. Findings of the study show students engaging in critical conversations without being directed into one way of thinking, which leads to significant improvement in their critical thinking. This further shows that texts that raise questions about different discourses can create an inclusive critical curriculum. It can be concluded that students can learn best when presented with a context they can identify with and are able to tap to their everyday experiences.